Blood Pressure Control in Hypertensive Patients in Federally Qualified Health Centers: Impact of Shared Decision Making in the Office-GAP Program. Issue 1 (July 2016) - Olomu, Adesuwa; Khan, Nazia Naz S.; Todem, David; Huang, Qinhua; Bottu, Shireesha; Qadri, Syeda; Holmes-Rovner, Margaret
Background: Hypertension (HTN) in people with diabetes doubles the risk of cardiovascular disease. Prior patient activation studies largely show improved communication but little impact on behavior or health outcomes. We sought to 1) assess the impact of Office-Based Guidelines Applied to Practice (Office-GAP) Program on blood pressure (BP) control; 2) determine the rate and predictors of BP control in patients with HTN and/or diabetes mellitus (DM) in federally qualified health centers.Methods: Sample: Patients with coronary heart disease (CHD) and/or DM with history of HTN; analyzed patients with DM and HTN compared to HTN without DM. Intervention: Office-GAP included physician training, patient activation, and an Office-GAP decision checklist. Two-site intervention/control design; data collection at baseline and after 3, 6, and 12 months. Logistic regression with propensity scoring assessed impact on BP control over time.Results: Of 243 patients, HTN was present in 75% at baseline; 32% had BP controlled. Consistent trend showed Office-GAP slightly improved the rate of BP control across time, while the control arm showed a nonsignificant decrease in the rate of BP control across time, compared to baseline. BP improved at 6 months at the intervention site compared to control site (odds ratio = 2.92; 95% confidence interval = 1.11–7.69).Conclusion: BP control was better at the intervention site compared to the control site at 6 months. Office-GAP shows promise to implement guidelines-based patient-centered care that improves BP.